Application of power metering automation in online loss management. Issue 1 (1st October 2022) - Liu, Liyang
Abstract: The electric power industry is a very important fundamental industry in China's social and economic development and innovation project, which has an extremely crucial influence on the development and construction of traditional industries, construction industries and information technology fields. In order to accelerate the process of urbanization and construction of a well-off society, power-related enterprises should carry out scientific and standardized supervision and management on generation, transportation, transformation, configuration and the use of electricity, the aim is to ensure that they can comply with rule of the national standards and the needs of social development.